Human papillomavirus and risk factors for cervical adenocarcinoma in the state of Pernambuco, Brazil - Telma Maria Lubambo Costa; Sandra Heráclio; Melania Maria Ramos Amorim; Paulo Roberto Eleutério Souza; Natália Lubambo; Gustavo Fonseca de Albuquerque Souza; Alex Sandro Rolland Souza
Abstract Objectives: to determine the incidence of the main high oncogenic risk types of the human papillomavirus (HPV) ( 16, 18, 31 and 33) and the risk factors for cervical adenocarcinoma. Methods: a case-control study was carried out with 324 women (69 with adenocarcinoma and 260 healthy controls) between 2001 and 2014. Information on risk factors associated with adenocarcinomawere collected and the detection performed on HPVby using Polymerase Chain Reaction (PCR) method. Results: adenocarcinoma was associated with age ≥40 years old (OR=2.95; 95%CI=1.13-7.71), ≤3 years of schooling (OR=2.34; 95%CI=1.02-5.37), presence of HPV (OR=6.75; 95%CI=2.41-18.91),women in menopausal status (OR=4.76; 95%CI:1.70-13.31) black race (OR=6.71; 95%CI= 2.11-21.32) and never had undergone cervical cancer screening (OR=9.92; 95%CI:2.41-40.81). Andamong the HPV types detected, HPV 18 was observed to be strongly associated with adenocarcinoma of the cervix (OR=99.1; 95%CI=12.96-757.78). Conclusions: the factors associated with cervical adenocarcinoma were ≥40 years old, ≤3 years of schooling, black race, menopausal status, never had undergone cervical cancer screening and the presence of HPV.